The IGF1 small dog haplotype is derived from Middle Eastern grey wolves: a closer look at statistics, sampling, and the alleged Middle Eastern origin of small dogs - Klütsch, Cornelya FC (BioMed Central, 2010)
This paper is a response to Gray MM, Sutter NB, Ostrander EA, Wayne RK: The IGF1 small dog haplotype is derived from Middle Eastern grey wolves. BMC Biology 2010, 8:16. See research article at http://www.biomedcentral.com/1741-7007/8/16.